Impact of right ventricular dysfunction after MitraClip treatment as a bridge to heart transplantation: insights from the MitraBridge registry. (14th October 2021) - Munafo, A; Scotti, A; Estevez-Loureiro, R; Arzamendi, D; Fam, N.P; Maffeo, D; Adamo, M; Ooms, J.F; Potena, L; Petronio, A.S; Grasso, C; Praz, F; et al.
Abstract: Background: MitraClip treatment has been recently proposed as a "bridge strategy" solution for advanced heart failure (HF) patients with significant functional mitral regurgitation (MR), who are potential candidates or are waiting for cardiac replacement therapy (LVAD or heart transplantation, HTx). In this clinical scenario, left-ventricular-related right ventricular dysfunction (RVD) represents an important prognostic factor. Purpose: Our study aimed to investigate the possible prognostic implication of RVD in advanced HF patients treated with MitraClip as a bridge to HTx strategy. Methods: RVD was assessed using the relationship between tricuspid annular peak systolic excursion (TAPSE) and pulmonary artery systolic pressure (PASP). All patients from the MitraBridge registry for whom these two echocardiographic parameters were available, were included in the study. A cut-off value of TAPSE/PASP ratio <0.36 was used to defined RVD, as previously reported. The primary outcome was a composite end-point of all-cause death or rehospitalization for HF at 2-year. For patients who underwent LVAD implantation or HTx, follow-up data were censored at the time of those events. Results: A total of 80 patients were included in the study. The median TAPSE/PASP ratio was 0.35 (25th-75th: 0.27–0.46), with 43 (54%) patients having a TAPSE/PASP ratio <0.36 (RVD group). The latter had a prevalent MR ischemic etiology (49% vs 38%), with a more frequent history of percutaneous coronary intervention (46.5% vs 22%, p=0.02). Except for TAPSE (15.7±3.6 mm vs 19.2±3.7 mm, p=0.001) and PASP (61±14 mmHg vs 39.5±9.5 mmHg, p<0.001), the other echocardiographic characteristics were similar between the two study groups (overall mean left ventricular ejection fraction 26.9±8%, median left ventricular end-diastolic volume index 120.7, 25th-75th: 102.2–146.5 mL/m 2 ). After a median follow-up time of 508 (25th-75th: 160–899) days, elective HTx occurred in 12 patients (7 from the RVD group), while LVAD implantation was performed in 13 patients (7 from the RVD group). The primary outcome occurred in 30 patients (38%) with a 2-year Kaplan-Meier estimate of freedom from the composite end-point of 41%. At univariate (HR 1.3 95% CI 0.6–2.8, p=0.451) and multivariate (HR 1.6 CI 0.7–3.8, p=0.249) Cox-regression analysis, TAPSE/PASP ratio <0.36 was not identified as an independent predictor of primary outcome. Indeed, at follow-up echocardiographic control (median time 252, 25th-75th: 122–365 days), a significant improvement in TAPSE/PASP ratio was observed in the RVD group (baseline median TAPSE/PASP ratio 0.27, 25th-75th: 0.22–0.32 vs follow-up median TAPSE/PASP ratio 0.37, 25th-75th: 0.28–0.47, p<0.001). Conclusion: In advanced HF patients with functional MR, MitraClip treatment could prevent or ameliorate left-ventricular-related RVD, allowing safe access to HTx or LVAD. Funding Acknowledgement: Type of funding sources: None.